Influence of environmental conditions on microstructure development and swelling in irradiated austenitic stainless steels - Voyevodin, V.N.; Garner, F.; Lazarev, N.P.; Kalchenko, A.S.; Udalova, N.A. (Вопросы атомной науки и техники, 2005)
Investigation and analysis of environmental conditions and swelling behaviour in irradiated austenitic stainless steels were done. Influence of dose rate, effects of stress and temperature history on microstructural evolution and swelling behaviour was studied in these steels. Досліджені і проаналізовані зовнішні умови, що впливають на поведінку розпухання опромінених аустенітних нержавіючих сталей. Вивчено вплив швидкості створення зсувів, зовнішніх напруг і температурної історії на мікроструктурну еволюцію і розпухання в цих сталях. Исследованы и проанализированы внешние условия, влияющие на поведение распухания облученных аустенитных нержавеющих сталей. Изучено влияния скорости создания смещений, внешних напряжений и температурной истории на микроструктурную эволюцию и распухание в этих сталях.